2022
DOI: 10.3390/ijms231911698
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Imaging Reveals Dynamic Reticular Cytoophidia

Abstract: CTP synthase (CTPS) can form filamentous structures termed cytoophidia in cells in all three domains of life. In order to study the mesoscale structure of cytoophidia, we perform fluorescence recovery after photobleaching (FRAP) and stimulated emission depletion (STED) microscopy in human cells. By using an EGFP dimeric tag as a tool to explore the physical properties of cytoophidia, we find that cytoophidia are dynamic and reticular. The reticular structure of CTPS cytoophidia may provide space for other comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…This analysis revealed that cytoophidia are dynamic and reticular, with the reticular structure of CTPS cytoophidia potentially providing space for other components [25], such as inosine monophosphate dehydrogenase (IMPDH), another enzyme capable of cytoophidia formation [29]. Curiously, in their structural analysis, the authors also observed CTPS granules with tentacles [25].…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…This analysis revealed that cytoophidia are dynamic and reticular, with the reticular structure of CTPS cytoophidia potentially providing space for other components [25], such as inosine monophosphate dehydrogenase (IMPDH), another enzyme capable of cytoophidia formation [29]. Curiously, in their structural analysis, the authors also observed CTPS granules with tentacles [25].…”
mentioning
confidence: 91%
“…A series of two papers from the group headed by Ji-Long Liu is dedicated to the analysis of cytoophidia, filamentous structures formed by the CTP synthase (CTPS) [25,26]. Cytoophidia, or "cellular snakes", are evolutionary conserved MLOs found in the cells of many species in all three domains of life and represent an interesting case of metabolic regulation via enzyme filamentation and resulting compartmentalization [27,28].…”
mentioning
confidence: 99%
See 2 more Smart Citations